2017
DOI: 10.1002/cbic.201700255
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Kinase Isoforms through Orthogonal and Chemical Inducible Signaling Cascades

Abstract: Interference from endogenous signaling enzymes represents a major hurdle for building orthogonal signaling cascades inside cells, particularly among closely related isoforms within an enzyme family. Here, we employed a genetically encoded chemical decaging strategy to build orthogonally activated kinase isoforms, with the endogenous counterparts temporally disabled by an extracellularly delivered bacterial effector. This approach eliminated any potential interference from other kinase isoforms as well as endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We then employed a luciferase reporter, SRE-luc, to monitor OspF activity in living cells. 31 SRE-luc reporter responds to ERK/MAPK signaling, allowing the luciferase expression level correlated with the endogenous ERK activity. For example, the reactivated OspF* attenuated ERK activity constitutively and thus reduced luciferase expression and the bioluminescence signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then employed a luciferase reporter, SRE-luc, to monitor OspF activity in living cells. 31 SRE-luc reporter responds to ERK/MAPK signaling, allowing the luciferase expression level correlated with the endogenous ERK activity. For example, the reactivated OspF* attenuated ERK activity constitutively and thus reduced luciferase expression and the bioluminescence signal.…”
Section: Resultsmentioning
confidence: 99%
“…First, we showed that, upon photoactivation of OspF* inside cells, the attenuation of ERK/p38 phosphorylation was observed as fast as 5 min (Figure S8) while the protein level of OspF* was not changed even 60 min after photoactivation. We then employed a luciferase reporter, SRE-luc, to monitor OspF activity in living cells . SRE-luc reporter responds to ERK/MAPK signaling, allowing the luciferase expression level correlated with the endogenous ERK activity.…”
Section: Resultsmentioning
confidence: 99%
“…By using trans ‐cyclooctene‐caged‐lysine groups (Scheme B), it was possible not only to control the function of proteins in cells but also in live mice . This chemistry also enabled kinase signaling pathways in cells to be controlled …”
Section: Applications Of Dissociative Bioorthogonal Reactions In the mentioning
confidence: 99%
“…[84] This chemistry also enabledk inase signaling pathways in cells to be controlled. [85] It is also possible to control cell-cell communication by bioorthogonal release reactions. An epitope with ac aged azidolysine residue was loaded onto major histocompatibility complex class I( MHC-I) on dendritic cells.…”
Section: Using Dissociative Chemistry To Control the Activityo F Protmentioning
confidence: 99%
“…For example, several protecting groups can be removed bioorthogonally inside live mammalian cells, and these chemistries have been used to switch on protein function by genetic code expansion. Intracellular bioorthogonal reactions that have been used in this purpose include inverse electron demand Diels–Alder reactions [18,59–61], 1,3-dipolar cycloadditions [62], Staudinger reactions [63], and palladium-catalysed propargyl removal (Table 4) [57]. Currently, all of these have only been demonstrated in caged lysine molecules ( 61 , 70 , 71 , 85 ) through a number of examples, including activation of luciferases, kinases, nucleases etc.…”
Section: Small-molecule Induced Activation or Inhibitionmentioning
confidence: 99%